Некоторые возможности применения Калифорния - Гэрбиш, Ш.; Ганболд, Г.; Балжинням, Н. (Scientific transaction of the National University of Mongolia. Physics, 2022)
Californium was first produced by Stanley G. Thompson, Glenn T. Seaborg, Kenneth Street, Jr. and Albert Ghiorso working at the University of California, Berkeley, in 1950. The technologies of neutron sources production developed by RIAR are reviewed. To produce 252Cf-containing core, different techniques are used depending on the source type. They are: impregnation of foam-alundum billets, glass beads and cermets production (point sources), electroplating on the platinum cathode (linear sources). Neutron sources produced by RIAR are one- or two-capsule design. Capsules are made of stainless steel and argon arc-welded. Neutron output of the sources varies from 1 x 10 to 2 x ю10 cm-2 s-1. Sources are widely used in medicine, industry, and research work. These isotopes of element 116 are the decay daughters of element 118 isotopes, which are produced via the 249Cf+48Ca reaction